Deferred sale (Bai' Mu'ajjal/Bai' bi Thaman Ajil (BBA)): its origin and validity from a Maqasid Shari'ah perspective - Ali, Mohammed Farid (IIUM Press, International Islamic University Malaysia, 2018)
Deferred sale (Bai’ mu’ajjal), in the Islamic Banking and Finance world widely known as Bai’ bi thaman ajil (BBA), is used as an extension to Profit-sale (Bai’ murabahah); both sales complement each other. The Profitsale sells the commodity with profit over the cost price, and BBA plays the role of receiving that payment on deferred or installment basis. BBA has become the “premier consumer financing facility” for the Islamic financial institutions(IFIs). This paper deals with deferred sale precisely. It looks into its origin and its transition from void to valid sale. Its application as trade contract and its modern application as financing tool is analysed in the light of the maqāṣid Sharīʿah.